Pengaruh Celebrity Endorsment, Brand Experience Dan E-Wom Terhadap Keputusan Pembelian Produk Skincare Ms Glow (Studi Kasus Pada Konsumen Ms Glow di Kota Malang) - Shinta Amalia Putri Fauzia; Siti Asiyah; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect of celebrity endorsements, brand experience and E-WOM on purchasing decisions for Ms Glow skincare products for Ms Glow consumers in Malang City. This research uses explanatory research method with a quantitative approach. The sampling technique used the incidental sampling technique which was carried out in Malang City using the Malhotra formula, namely the number of indicators multiplied by 5 so that a sample of 75 respondents was obtained. Data collection techniques using online questionnaires. Methods of data analysis using validity test, reliability test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis with SPSS analysis tool. Hypothesis testing uses the F test for simultaneous testing and the t test for partial testing. The results of this study indicate that celebrity endorsements, brand experience and E-WOM simultaneously influence purchasing decisions. Partially celebrity endorsements, brand experience and E-WOM have a positive and significant effect on purchasing decisions and the coefficient of determination (Adjusted R2) is 0.760 or 76.0%. Keywords: Celebrity Endorsement, Brand Experience, E-WOM, Purchase Decision